(untitled) (Fiep Bulletin - online, 2012)
Nowadays, adolescents are the target of many studies in all world, due the preoccupation about the possibility of future health problems because of sedentary lifestyle and irregular eating habits. The aim of this study was to determine the prevalence of cardiovascular risk factors in adolescents university students. It is a cross-sectional study developed with 300 adolescents enrolled in the first year of graduation courses of different areas in public institutions of higher education in the city of Maringá - PR. The data were collected through semi-structured interview, anthropometric measurements (weight, height and abdominal circumference) and were realized blood pressure measurements. The descriptive analysis included measures of central tendency and dispersion (mean and standard deviation), besides the absolute and relative frequency of the variables was used Chi-square and Fischer’s Exact Test to assess the association of the variables between the genders. The results showed that boys had all the means of anthropometric variables and blood pressure higher than girls, except a lower BMI, the risk factors most prevalent in young university students were sedentary (57.3%) and consumption of alcoholic beverages (59.3%). Our findings highlight the need of an encouragement to healthy behaviors and thereby minimize possible future health hazards.